A PBAT-PLA composite material and its application in a biodegradable heat-shrinkable film

PBAT-PLA composite material was prepared by cross-linking PBAT and polyadipic acid-butadiene terephthalate by three-layer coextrusion blow molding, which solved the problem of difficult to take into account both material performance and biodegradability in the prior art, and achieved high-performance and high-biodegradation heat shrink film and packaging film.

CN115891367BActive Publication Date: 2025-06-03SHANGONG HUAYE PACKING MATERIALS CO LTD

Patent Information

Application Number
CN202211431074.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2025-06-03
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

In the prior art, when developing biodegradable heat shrink films and degradable packaging films, it is difficult to simultaneously improve the tensile properties, impact resistance and biodegradability of the material.

Method used

PBAT-PLA composite was prepared by cross-linking PBAT with polyadipic acid-butadiene terephthalate by three-layer coextrusion blow molding, and the compatibility and interface strength of polylactic acid and PBAT were improved by thiol grafting and allylation reactions.

Benefits of technology

The excellent performance of PBAT-PLA composite in biodegradable heat shrink film and degradable packaging film was achieved, including high tensile strength, good impact resistance and high biodegradation rate, achieving a biodegradation rate of 96.2%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115891367B_ABST
    Figure CN115891367B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of degradable materials, and discloses a PBAT-PLA composite material and its application in a biodegradable heat-shrinkable film. Poly(butylene adipate-co-terephthalate) (PBAT) grafted with maleic anhydride and mercaptoethylamine are subjected to amidation and thermal imidization reactions to synthesize mercapto-grafted PBAT, thereby introducing mercapto groups into the side chains of PBAT. Then, it is subjected to a UV cross-linking reaction with allyl-terminated polylactic acid to obtain PLA-crosslinked PBAT, significantly improving the compatibility between polylactic acid and PBAT, with higher interfacial strength. Using PBAT as the inner and outer layers and PLA-crosslinked PBAT as the intermediate layer, the PBAT-PLA composite material prepared by three-layer coextrusion blow molding has excellent tensile properties and impact resistance and other properties when made into a biodegradable heat-shrinkable film through a blow molding process, and has broad development and applications in biodegradable packaging films, heat-shrinkable films, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of degradable materials, and particularly to a PBAT-PLA composite material and its application in a biodegradable heat shrinkable film. Background Art

[0002] In recent years, the development of film materials such as biodegradable packaging films and biodegradable heat shrinkable films is of great significance for alleviating the energy crisis and environmental pollution. Polylactic acid is a polymer material with excellent biodegradability and biocompatibility. By compounding polylactic acid with materials such as poly(butylene adipate-co-terephthalate), a degradable material with excellent comprehensive properties is obtained, which has broad application prospects in the fields of packaging films, heat shrinkable films, etc. For example, Chinese patent document CN103589124B, "A fully biodegradable PLA / PBAT composite film and its preparation method", discloses that PLA and PBAT are blended, and by taking advantage of the complementary performance advantages of the two and adjusting the blending ratio of the two, a blend with higher strength and good flexibility can be obtained. The film prepared from the blend can achieve full biodegradation and is an environmentally friendly material.

[0003] Poly(butylene adipate-co-terephthalate) (PBAT) has excellent chemical resistance, mechanical properties, etc., and is widely used in packaging films, heat shrinkable films, composite films, etc. The present invention aims to synthesize crosslinked PLA-PBAT, perform three-layer coextrusion blow molding on poly(butylene adipate-co-terephthalate), and apply it to the fields of biodegradable heat shrinkable films, degradable packaging films, etc. Summary of the Invention

[0004] (I) Technical Problems to be Solved

[0005] The present invention performs coextrusion blow molding on crosslinked PLA-PBAT and poly(butylene adipate-co-terephthalate) to obtain a composite material with excellent comprehensive properties, which is applied to the fields of biodegradable heat shrinkable films, degradable packaging films, etc.

[0006] (II) Technical Solutions

[0007] To achieve the above object, the present invention provides the following technical solutions: A PBAT-PLA composite material, wherein the PBAT-PLA composite material takes PBAT as the inner layer and the outer layer, and crosslinked PLA-PBAT as the middle layer, and is prepared by three-layer coextrusion blow molding. The process flow of the coextrusion blow molding is as follows: plasticization by an extruder, three-layer coextrusion and superposition die head, water ring cooling, traction roller, oven preheating, tube ring biaxial stretching, air ring cooling, NDC film measuring device, traction roller, preheating roller, winding roller, storage of large roll film, and slitting into roll film.

[0008] Preferably, the preparation process of the crosslinked PLA-PBAT is as follows:

[0009] S1. Dissolve 100 parts by weight of poly(butylene adipate-co-terephthalate) grafted maleic anhydride in a solvent, then add 6 - 15 parts by weight of mercaptoethylamine, and react in a nitrogen atmosphere. After precipitation, filtration, and washing, mercapto-grafted PBAT is obtained.

[0010] S2. Dissolve 100 parts by weight of double-ended hydroxyl poly(lactic acid) in dichloromethane, add 12 - 25 parts by weight of N,N'-carbonyldiimidazole, and react at 35 - 50 °C for 6 - 18 h. After precipitation, filtration, and washing, double-ended imidazolyl ester poly(lactic acid) is obtained.

[0011] S3. Dissolve 100 parts by weight of double-ended imidazolyl ester poly(lactic acid) in dimethyl sulfoxide, add 4 - 7 parts by weight of allyl alcohol and 5 - 10 parts by weight of triethylamine, and react at 40 - 50 °C for 24 - 48 h. After precipitation, filtration, and washing, double-ended allyl poly(lactic acid) is obtained.

[0012] S4. Add 60 - 200 parts by weight of double-ended allyl poly(lactic acid) and 100 parts by weight of mercapto-grafted PBAT to N,N-dimethylformamide, stir to dissolve and dropwise add 1.2 - 2 parts by weight of dimethyl benzoyl peroxide, and stir for cross-linking reaction. After precipitation, filtration, and washing, PLA cross-linked PBAT is obtained.

[0013] Preferably, the solvent in (1) includes xylene, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0014] Preferably, in the reaction of (1), first react at 25 - 35 °C for 3 - 8 h, and then raise the temperature to 120 - 140 °C for reflux reaction for 6 - 12 h.

[0015] Preferably, the reaction in (4) is carried out by ultraviolet light irradiation for 1 - 3 h.

[0016] Preferably, the application of the PBAT-PLA composite material in a biodegradable heat-shrinkable film.

[0017] (III) Beneficial technical effects

[0018] Compared with the prior art, the present invention has the following beneficial technical effects:

[0019] The thiol-grafted PBAT was synthesized by subjecting poly(butylene adipate-co-terephthalate) (PBAT) grafted with maleic anhydride to amidation and thermal imidization reactions with 2-mercaptoethylamine, thereby introducing thiol groups into the side chains of PBAT. The double-ended thiol-terminated polylactic acid was activated with N,N'-carbonyldiimidazole and then reacted with allyl alcohol to obtain double-ended allyl-terminated polylactic acid, which was then subjected to ultraviolet cross-linking reaction with thiol-grafted PBAT to obtain PLA-crosslinked PBAT, significantly improving the compatibility between polylactic acid and PBAT and having a higher interfacial strength. Using PBAT as the inner and outer layers and PLA-crosslinked PBAT as the intermediate layer, the PBAT-PLA composite material prepared by three-layer coextrusion blow molding can be blown into a degradable heat-shrinkable film, which has excellent tensile properties and impact resistance. After chemically cross-linking polylactic acid and PBAT, when polylactic acid undergoes biodegradation, the molecular chains of PLA-crosslinked PBAT can be broken and fractured, thus promoting the biodegradation of the composite film and expanding its development and application in degradable packaging films, heat-shrinkable films, etc. Description of the Drawings

[0020] Figure 1 is the preparation process route of thiol-grafted PBAT.

[0021] Figure 2 is the preparation process route of PLA-crosslinked PBAT.

[0022] Figure 3 is the process flow chart of blowing a degradable heat-shrinkable film from the PBAT-PLA composite material. Detailed Embodiments

[0023] Referring to the literature "Study on Chain Extension of Hydroxyl-Terminated Polylactic Acid with TDI" in the 6th issue of the 25th volume of the journal "Polyurethane Industry" in 2010, double-ended hydroxyl-terminated polylactic acid was prepared: 10 g of D,L-lactic acid and 10 mg of the end-capping agent 1,4-butanediol were subjected to vacuum distillation and pre-polymerized at 125 °C for 3 h, then 80 mg of stannous octoate was added, the temperature was raised to 170 °C, and melt polycondensation was carried out for 8 h. The crude product was dissolved in chloroform and precipitated with ethanol to obtain double-ended hydroxyl-terminated polylactic acid.

[0024] Referring to the literature "Effect of PBAT-g-MA on the Properties of Thermoplastic Starch Poly(butylene adipate-co-terephthalate) Blends" in the 8th issue of the 44th volume of the journal "China Plastics Industry" in August 2016, poly(butylene adipate-co-terephthalate) grafted with maleic anhydride was prepared: 3 g of poly(butylene adipate-co-terephthalate), 0.02 g of diisopropylbenzene peroxide, and 0.15 g of maleic anhydride were added to a rheometer. After the torque was stabilized, the material was added to dichloromethane and precipitated with methanol to obtain poly(butylene adipate-co-terephthalate) grafted with maleic anhydride.

[0025] Example 1

[0026] (1) Dissolve 5 g of polybutylene adipate-co-terephthalate grafted maleic anhydride into 100 mL of xylene solvent, then add 0.3 g of mercaptoethylamine. React in a nitrogen atmosphere at 25 °C for 8 h first, and then raise the temperature to 140 °C for reflux reaction for 6 h. After the reaction, cool and add acetone for precipitation, filter the solvent, and wash with acetone and ethanol in sequence to obtain mercapto-grafted PBAT.

[0027] (2) Dissolve 2 g of double-ended hydroxyl polylactic acid into 50 mL of dichloromethane, add 0.24 g of N,N-carbonyldiimidazole, and react at 40 °C for 12 h. After the reaction, add ethanol for precipitation, filter the solvent, and wash the product with ethanol to obtain double-ended imidazolyl ester polylactic acid.

[0028] (3) Dissolve 2 g of double-ended imidazolyl ester polylactic acid into 50 mL of dimethyl sulfoxide, add 0.12 g of allyl alcohol and 0.1 g of triethylamine, and react at 50 °C for 24 h. After the reaction, add ethanol for precipitation, filter the solvent, and wash the product with distilled water and ethanol in sequence to obtain double-ended allyl polylactic acid.

[0029] (4) Add 1.2 g of double-ended allyl polylactic acid and 2 g of mercapto-grafted PBAT into 200 mL of N,N-dimethylformamide, stir to dissolve and dropwise add 24 mg of dimethoxybenzil. Carry out crosslinking reaction for 2 h by ultraviolet light irradiation and stirring. After the reaction, add ethanol for precipitation, filter the solvent, and wash the product with distilled water and ethanol in sequence to obtain PLA crosslinked PBAT.

[0030] (5) Using PBAT as the inner and outer layers and PLA crosslinked PBAT as the middle layer, prepare by three-layer coextrusion blow molding. The process flow of coextrusion blow molding is plasticization by an extruder, three-layer coextrusion and superposition die head, water ring cooling, traction roller, oven preheating, tube ring biaxial stretching, air ring cooling, NDC film measuring device, traction roller, preheating roller, winding roller, storage of large roll film, slitting into roll film, to obtain PBAT-PLA composite material, and blow it into a degradable heat shrinkable film.

[0031] Example 2

[0032] (1) Dissolve 5 g of polybutylene adipate-co-terephthalate grafted maleic anhydride into 50 mL of N,N-dimethylacetamide solvent, then add 0.6 g of mercaptoethylamine. React in a nitrogen atmosphere at 35 °C for 5 h first, and then raise the temperature to 130 °C for reflux reaction for 12 h. After the reaction, cool and add acetone for precipitation, filter the solvent, and wash with acetone and ethanol in sequence to obtain mercapto-grafted PBAT.

[0033] (2) Dissolve 2 g of dihydroxy-terminated polylactic acid in 60 mL of dichloromethane, add 0.5 g of N,N'-carbonyldiimidazole, react at 50 °C for 12 h, add ethanol for precipitation after the reaction, filter the solvent, wash the product with ethanol to obtain diimidazolyl-ester-terminated polylactic acid.

[0034] (3) Dissolve 2 g of diimidazolyl-ester-terminated polylactic acid in 30 mL of dimethyl sulfoxide, add 0.14 g of allyl alcohol and 0.15 g of triethylamine, react at 50 °C for 36 h, add ethanol for precipitation after the reaction, filter the solvent, wash the product with distilled water and ethanol in sequence to obtain diallyl-terminated polylactic acid.

[0035] (4) Add 2.5 g of diallyl-terminated polylactic acid and 2 g of mercapto-grafted PBAT to 400 mL of N,N-dimethylformamide, stir to dissolve and dropwise add 32 mg of dimethoxybenzil, carry out crosslinking reaction for 2 h by ultraviolet irradiation and stirring, add ethanol for precipitation after the reaction, filter the solvent, wash the product with distilled water and ethanol in sequence to obtain PLA-crosslinked PBAT.

[0036] (5) Using PBAT as the inner and outer layers and PLA-crosslinked PBAT as the middle layer, it is prepared by three-layer coextrusion blow molding. The process flow of coextrusion blow molding is plasticization by an extruder, three-layer coextrusion and superposition die head, water ring cooling, haul-off roll, oven preheating, tube ring biaxial stretching, air ring cooling, NDC film measuring device, haul-off roll, preheating roll, winding roll, storage of large roll film, slitting into roll film to obtain PBAT-PLA composite material, and blown into a degradable heat-shrinkable film.

[0037] Example 3

[0038] (1) Dissolve 5 g of poly(butylene adipate-co-terephthalate) grafted maleic anhydride in 100 mL of N,N-dimethylformamide solvent, then add 0.6 g of mercaptoethylamine, react in a nitrogen atmosphere at 35 °C for 8 h first, then raise the temperature to 120 °C for reflux reaction for 6 h, cool and add acetone for precipitation after the reaction, filter the solvent, wash with acetone and ethanol in sequence to obtain mercapto-grafted PBAT.

[0039] (2) Dissolve 2 g of dihydroxy-terminated polylactic acid in 50 mL of dichloromethane, add 0.5 g of N,N'-carbonyldiimidazole, react at 50 °C for 12 h, add ethanol for precipitation after the reaction, filter the solvent, wash the product with ethanol to obtain diimidazolyl-ester-terminated polylactic acid.

[0040] (3) Dissolve 2 g of bis - terminal imidazolyl - ester - based polylactic acid in 50 mL of dimethyl sulfoxide, add 0.14 g of allyl alcohol and 0.2 g of triethylamine, react at 50 °C for 24 h. After the reaction, add ethanol to precipitate, filter the solvent, and wash the product with distilled water and ethanol successively to obtain bis - terminal allyl - based polylactic acid.

[0041] (4) Add 4 g of bis - terminal allyl - based polylactic acid and 2 g of mercapto - grafted PBAT to 400 mL of N,N - dimethylformamide, stir to dissolve and add 40 mg of dimethylbenzoin ether. Carry out cross - linking reaction for 3 h by ultraviolet light irradiation and stirring. After the reaction, add ethanol to precipitate, filter the solvent, and wash the product with distilled water and ethanol successively to obtain PLA - crosslinked PBAT.

[0042] (5) Using PBAT as the inner and outer layers and PLA - crosslinked PBAT as the middle layer, it is prepared by three - layer co - extrusion blow - molding. The process flow of co - extrusion blow - molding is: plasticization by an extruder, three - layer co - extrusion and superposition die head, water - ring cooling, traction roll, oven pre - heating, tube - ring biaxial stretching, air - ring cooling, NDC film measuring device, traction roll, pre - heating roll, winding roll, storage of large - roll film, slitting into roll film, to obtain PBAT - PLA composite material, and blown into a degradable heat - shrinkable film.

[0043] Example 4

[0044] (1) Dissolve 5 g of poly(butylene adipate - terephthalate) grafted maleic anhydride in 100 mL of N,N - dimethylformamide solvent, then add 0.5 g of mercaptoethylamine, react in a nitrogen atmosphere at 25 °C for 6 h first, then heat up to 120 °C and reflux for 6 h. After the reaction, cool and add acetone to precipitate, filter the solvent, and wash with acetone and ethanol successively to obtain mercapto - grafted PBAT.

[0045] (2) Dissolve 2 g of bis - terminal hydroxyl - based polylactic acid in 50 mL of dichloromethane, add 0.3 g of N,N - carbonyldiimidazole, react at 40 °C for 12 h. After the reaction, add ethanol to precipitate, filter the solvent, and wash the product with ethanol to obtain bis - terminal imidazolyl - ester - based polylactic acid.

[0046] (3) Dissolve 2 g of bis - terminal imidazolyl - ester - based polylactic acid in 40 mL of dimethyl sulfoxide, add 0.1 g of allyl alcohol and 0.12 g of triethylamine, react at 40 °C for 24 h. After the reaction, add ethanol to precipitate, filter the solvent, and wash the product with distilled water and ethanol successively to obtain bis - terminal allyl - based polylactic acid.

[0047] (4) Add 3 g of diallyl-terminated polylactic acid and 2 g of mercapto-grafted PBAT to 400 mL of N,N-dimethylformamide, stir to dissolve and add 30 mg of dimethyl benzyl ketal. Carry out the crosslinking reaction for 3 h by irradiating with ultraviolet light and stirring. After the reaction, add ethanol to precipitate, filter the solvent, and wash the product with distilled water and ethanol in turn to obtain PLA-crosslinked PBAT.

[0048] (5) Using PBAT as the inner and outer layers and PLA-crosslinked PBAT as the middle layer, prepare by three-layer coextrusion blow molding. The process flow of coextrusion blow molding is plasticization by an extruder, three-layer coextrusion and superposition die head, water ring cooling, haul-off roll, oven preheating, tube ring biaxial stretching, air ring cooling, NDC film measuring device, haul-off roll, preheating roll, winding roll, storage of large roll film, slitting into roll film, to obtain the PBAT-PLA composite material, and blow it into a degradable heat-shrinkable film.

[0049] Comparative Example 1

[0050] (1) Using PBAT as the inner and outer layers and polylactic acid as the middle layer, prepare by three-layer coextrusion blow molding. The process flow of coextrusion blow molding is plasticization by an extruder, three-layer coextrusion and superposition die head, water ring cooling, haul-off roll, oven preheating, tube ring biaxial stretching, air ring cooling, NDC film measuring device, haul-off roll, preheating roll, winding roll, storage of large roll film, slitting into roll film, to obtain the PBAT-PLA composite material, and blow it into a degradable heat-shrinkable film.

[0051] Refer to the GB / T 1040.1-2018 standard to measure the tensile properties of the biodegradable heat-shrinkable film. The specimen of the biodegradable heat-shrinkable film is 120 mm×30 mm×4 mm, and the tensile rate is 100 mm / min.

[0052] Refer to the GB / T 1843-2008 standard to measure the impact resistance of the biodegradable heat-shrinkable film. The specimen of the biodegradable heat-shrinkable film is 120 mm×30 mm×4 mm.

[0053] Tensile strength (MPa) Elongation at break (%) <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 52.7 49.8 11.8 Example 2 69.5 42.6 13.1 Example 3 58.2 63.2 14.2 Example 4 53.1 61.0 11.7 Comparative Example 1 40.1 43.9 9.5

[0054] Using PLA-crosslinked PBAT and poly(butylene adipate-co-terephthalate) for three-layer coextrusion blow molding, the tensile strength of the modified poly(butylene adipate-co-terephthalate) reaches 52.7-69.5 MPa, the elongation at break reaches up to 63.2%, and the impact strength reaches 11.7-14.2 kJ / m 2 .

[0055] Refer to the standard of GB / T 19277.1-2011, conduct a compost degradation test on the PBAT-PLA composite degradable heat-shrinkable film, and use a total organic carbon analyzer for determination to measure the CO 2 emission of the PBAT-PLA composite degradable heat-shrinkable film under composting, and calculate the ultimate aerobic biodegradation performance.

[0056] Mix 1000 g of culture soil evenly with 50 g of PBAT-PLA composite material. Use 50 g of cellulose as the control group, add distilled water to adjust the relative humidity of the culture soil to 50%, and put it into a compost container after mixing evenly. Conduct a compost degradation experiment for 180 days in an experimental environment of 58 °C. Absorb the carbon dioxide generated in the experiment with an aqueous solution of NaOH, and determine the carbon dioxide release amount and calculate the degradation rate Q through titration analysis.

[0057] The calculation formula is as follows: Q = (T CO2 - B CO2 ) / Th CO2 × 100%, where T CO2 is the cumulative CO 2 emission of the experimental sample compost container; B CO2 is the cumulative CO 2 emission of the blank container; Th CO2 is the theoretically released CO 2 emission of the test sample.

[0058]

[0059] After the compost degradation test, the biodegradation rate of the PBAT-PLA composite degradable heat-shrinkable film reached a maximum of 96.2%.

Claims

1. A PBAT-PLA composite material, characterized in that: The PBAT-PLA composite material uses PBAT as the inner and outer layers, and PLA crosslinked PBAT as the middle layer, and is prepared by three-layer coextrusion blow molding. The process flow of coextrusion blow molding is plasticization by an extruder, three-layer coextrusion and superposition die head, water ring cooling, traction roller, oven preheating, tube ring biaxial stretching, air ring cooling, NDC film measuring device, traction roller, preheating roller, winding roller, storage of large roll film, and slitting into roll film; The preparation process of the PLA crosslinked PBAT is as follows: S1. Dissolve 100 parts by weight of polybutylene adipate-co-terephthalate grafted maleic anhydride in a solvent, then add 6-15 parts by weight of mercaptoethylamine, react in a nitrogen atmosphere, precipitate, filter, and wash to obtain mercapto-grafted PBAT; S2. Dissolve 100 parts by weight of dihydroxy-terminated polylactic acid in dichloromethane, add 12-25 parts by weight of N,N'-carbonyldiimidazole, react at 35-50 °C for 6-18 h, precipitate, filter, and wash to obtain diimidazolyl ester-terminated polylactic acid; S3. Dissolve 100 parts by weight of diimidazolyl ester-terminated polylactic acid in dimethyl sulfoxide, add 4-7 parts by weight of allyl alcohol and 5-10 parts by weight of triethylamine, react at 40-50 °C for 24-48 h, precipitate, filter, and wash to obtain diallyl-terminated polylactic acid; S4. Add 60-200 parts by weight of diallyl-terminated polylactic acid and 100 parts by weight of mercapto-grafted PBAT to N,N-dimethylformamide, stir to dissolve and dropwise add 1.2-2 parts by weight of dimethoxybenzil, stir to carry out crosslinking reaction, precipitate, filter, and wash to obtain PLA crosslinked PBAT.

2. A PBAT-PLA composite material according to claim 1, characterized in that: The solvent in S1 includes xylene, N,N-dimethylformamide, and N,N-dimethylacetamide.

3. A PBAT-PLA composite material according to claim 1, characterized in that: In S1, the reaction is first carried out at 25-35 °C for 3-8 h, and then the temperature is raised to 120-140 °C for reflux reaction for 6-12 h.

4. A PBAT-PLA composite material according to claim 1, characterized in that: In S4, the reaction is carried out by ultraviolet light irradiation for 1-3 h.

5. Application of a PBAT-PLA composite material according to any one of claims 1-4 in a biodegradable heat shrinkable film.

Citation Information

Patent Citations

  • A fully biodegradable PLA / PBAT composite film and its preparation method

    CN103589124B

  • Full-biodegradable heat shrink film and preparation method thereof

    CN115109397A

Cited By

  • Biodegradable shrink film as well as preparation method and application thereof

    CN121108702A